Neuromarketing: Current Applications in Favor of Consumerism - López, María Judith (2022)
Neuromarketing is an innovative branch of neuroscience that seeks to provide for the consumer’s wishes through the understanding of its brain structure, which will allow to comprehend and develop products or publicity that can be more attractive, new and attached to what has been created. Neuromarketing is integrated in this new digital age in an extraordinary way due to it having more opportunities to be applied. This science can be observed in each ad, which makes the individual feel the need to spend money on a product. Big companies have benefited from this almost-magic formula that allows the emotion and reasoning behind each purchase. Thanks to neuromarketing, each product could be attractive enough in the neuro-sensory aspect for it to be consumed, science being the only needed thing. This investigation provides the knowledge on the reason why it is one of the most researched sciences by the producer nowadays.